2022
DOI: 10.3389/fmed.2022.875298
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Stage Bedside Intubation Method to Improve Success Rate of Post-pyloric Placement of Spiral Nasoenteric Tubes in Critically Ill Patients: A Multi-Center, Prospective Study

Abstract: BackgroundsProkinetic agents could improve the success rate of post-pyloric placement of self-propelled spiral nasoenteric tubes (NETs), and bedside blind technique might apply as a rescue therapy subsequent to spontaneous transpyloric migration failure. The objective of this study was to investigated the validity and safety of these two bedside intubation methods as a sequential procedure for post-pyloric placement of spiral NETs in critically ill patients.MethodsThe multicenter, prospective study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Similarly, an international study found that nutritional support for CS patients was the least adequate compared with other types of surgery [25]. Clinical physicians have carried out many studies to try to improve this poor nutritional status in a variety of ways, including developing nutrition assessment tools [26-28], optimizing nutrition support pathways [29][30][31][32], and exploring the best combination of nutrients [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an international study found that nutritional support for CS patients was the least adequate compared with other types of surgery [25]. Clinical physicians have carried out many studies to try to improve this poor nutritional status in a variety of ways, including developing nutrition assessment tools [26-28], optimizing nutrition support pathways [29][30][31][32], and exploring the best combination of nutrients [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…However, this technique demands adequate training and advanced clinical skill, otherwise it is difficult to perform. 16 Another method is to place a feeding tube under endoscopic guidance, which has a higher success rate but is relatively expensive. 17 The purpose of this study is to compare the one-time success rate of blind and endoscopy-guided postpyloric feeding tube placement after implementing a comprehensive nursing scheme of intestinal blind placement.…”
Section: Introductionmentioning
confidence: 99%
“…Blind bedside insertion is a widely used technique for postpyloric placement in developing countries because it does not require expensive and sophisticated medical equipment. However, this technique demands adequate training and advanced clinical skill, otherwise it is difficult to perform 16 . Another method is to place a feeding tube under endoscopic guidance, which has a higher success rate but is relatively expensive 17 .…”
Section: Introductionmentioning
confidence: 99%